Historiefag og historiepolitik - Jensen, Bernard Eric (Slagmark - Tidsskrift for idéhistorie, 2018)
The article outlines how Danish academic historians have sought to handle questions concerning a politics of history – i.e. is it legitimate to use the writing of history for the purpose of pursuing presentday political goals? Three different ways of handling that issue are described, and it is argued that academic historians need to develop a more reflective and selfcritical approach to the task of writing history.